Manajemen 5S dalam Kinerja Lembaga Pendidikan - Rosita Endang Kusmaryani (Fakultas Ilmu Pendidikan UNY, 2008)
Education institute is a organization having import ant role in giving quality of education service, what as a whole holding responsible' yield quality of human resource. In education service management required by correct handling and checking, but which often happened is existence of human errors which be not parried. The mistake of man 'even affect at education institute performance in executing education serviceHuman errors actually can be eliminated if job process can be designed in such a manner by paying attention to man factors and work environment. In reaching the education management efficiency, 5S management as first step a management. 5S management is' a approach giving pressure at workplace organizing better. It is because basically resulted from by 'mistakes is man, besides coming from itself man also resulted from the work enviroument. Key words : 5S management, performance